SUPPLEMENTARY DATA RESEARCH ARTICLE: Chemical conjugations of Sgc8-c with the lymphoma drug dasatinib to generate selective biotherapeutics. (2021) - Sicco, Estefanía; Almeida, Lucía; Moreno, María; Calzada, Victoria; Cerecetto, Hugo
No abstract available